Silencing Heat Shock Protein 47 (HSP47) in Fibrogenic Precision-Cut Lung Slices: A Surprising Lack of Effects on Fibrogenesis? - Ruigrok, Mitchel J. R.; El Amasi, Khaled E. M.; Leeming, Diana J.; Sand, Jannie M. B.; Frijlink, Henderik W.; Hinrichs, Wouter L. J.; Olinga, Peter (Frontiers in Medicine, 2021)
Idiopathic pulmonary fibrosis (IPF) is a chronic disease that is characterized by the excessive deposition of scar tissue in the lungs. As currently available treatments are unable to restore lung function in patients, there is an urgent medical need for more effective drugs. Developing such drugs, however, is challenging because IPF has a complex pathogenesis. Emerging evidence indicates that heat shock protein 47 (HSP47), which is encoded by the gene Serpinh1, may be a suitable therapeutic target as it is required for collagen synthesis. Pharmacological inhibition or knockdown of HSP47 could therefore be a promising approach to treat fibrosis. The objective of this study was to assess the therapeutic potential of Serpinh1-targeting small interfering RNA (siRNA) in fibrogenic precision-cut lung slices prepared from murine tissue. To enhance fibrogenesis, slices were cultured for up to 144 h with transforming growth factor β1. Self-deliverable siRNA was used to knockdown mRNA and protein expression, without affecting the viability and morphology of slices. After silencing HSP47, only the secretion of fibronectin was reduced while other aspects of fibrogenesis remained unaffected (e.g., myofibroblast differentiation as well as collagen secretion and deposition). These observations are surprising as others have shown that Serpinh1-targeting siRNA suppressed collagen deposition in animals. Further studies are therefore warranted to elucidate downstream effects on fibrosis upon silencing HSP47.